(untitled) (Journal of Patan Academy of Health Sciences, 2020)
Health information and intelligence are important components of health care system. Moreover they are very crucial during disaster management. Collecting right information at right time and delivering it to right target at right time is important during disaster. During COVID-19, at Patan Hospital, the information management has been done through external communication officer who is a part of hospital incident command system.